Lied academies conducted by Thomas Hampson at the Music festival Heidelberger Frühling (2017-2019): Work on the repertoire of Ggerman songs - Ruseva, Mariya Rosenova (Young Scientific Music and Dance Forum : Conference with international participation, 2021)
Since 2006, the Hampsong Foundation has been working closely with the music festival Heidelberger Frühling, an annual co-production of master classes for young opera singers. In the last three years (2017-2019) they were lead by the baritone Thomas Hampson himself and were streamed through Facebook Live. Based on this video material (almost 60 hours) observations were made on Hampson’s methods of teaching and this article resumes important discussions about the Lied-genre in social and cultural aspect, Hampson’s vision about the art song as a metaphor of Human Being (Dasein), his approach to achieve better posture, breath, sound and diction of the participants. All these components aim to achieve better clarity and understanding of the poetic text, set into musical composition; they help the singers in finding their own way of interpretation.